2022
DOI: 10.1021/acs.inorgchem.2c01820
|View full text |Cite
|
Sign up to set email alerts
|

Drug Delivery Using Hydrophilic Metal–Organic Frameworks (MOFs): Effect of Structure Properties of MOFs on Biological Behavior of Carriers

Abstract: To study the influence of pore structural properties of metal−organic frameworks (MOFs) on drug adsorption and delivery, we synthesized two MOF termed TMU-6(RL1) {[Zn-(oba)(RL1) 0.5 ] n •(DMF) 1.5 } and TMU-21(RL2) {[Zn(oba)-(RL2) 0.5 ] n •(DMF) 1.5 } with amine basic N-donor pillars containing phenyl or naphthyl cores with various hydrophilic properties around the main center of the reaction. TG, IR, XPS, and PXRD analyses were used to extensively characterize the MOFs. The synthesized carriers showed high ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…MOFs are characterized by large specific surface areas, permanent pores, tunable pore diameters, and functions that can be modified according to needs [19,20]. As a result, MOFs have received considerable attention for their applications in gas storage, sensors, medicine, agronomy, and catalysis [21][22][23][24][25][26][27]. In recent years, MOF-based materials have been widely used for electrochemical energy storage systems.…”
Section: Introductionmentioning
confidence: 99%
“…MOFs are characterized by large specific surface areas, permanent pores, tunable pore diameters, and functions that can be modified according to needs [19,20]. As a result, MOFs have received considerable attention for their applications in gas storage, sensors, medicine, agronomy, and catalysis [21][22][23][24][25][26][27]. In recent years, MOF-based materials have been widely used for electrochemical energy storage systems.…”
Section: Introductionmentioning
confidence: 99%
“…These characteristics serve as essential features that can greatly enhance the efficiency of MOFs. [24][25][26][27] Liang et al demonstrated that hydrophilic MOFs show superior performance in terms of bioactivity retention of biomolecules. 28 However, the impact of MOF hydrophilicity and hydrophobicity on drug solubility and controlled release remains uncertain and require further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Metal–organic frameworks (MOFs) represent a class of crystalline porous materials with periodic extended structures, which consist of metal nodes (metal ions or metal clusters) self-assembled with organic ligands through coordination bonds. , Owing to the intriguing physical/chemical properties with rich coordination modes, MOFs have attracted increasing attention in catalysis, gas adsorption, energy storage, drug release, biosensing, fluorescence sensing, , etc. Especially, the ultrahigh porosity and large specific surface area of MOFs facilitate the efficient transport of the analytes, affording the promising electrochemical glucose sensors. MOFs based on benzodicarboxylic acid (BDC) and 1,3,5-benzenetricarboxylic acid (BTC) have been attempted in electrochemical sensing. , However, Ni-BDC is restricted by a high detection limit and slow reaction kinetics, while Cu-BTC shows a narrow detection range. Accordingly, the rational design of functional ligands is essential for high-performance MOF-based sensors.…”
Section: Introductionmentioning
confidence: 99%